ANALISIS KINERJA KEUANGAN KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) KECAMATAN PAMBOANG KABUPATEN MAJENE - Azisah, Nur; Azis, Muhammad; Afiah, Nur (Institut Teknologi dan Bisnis Swadharma, 2024)
This research aims to analyze the financial performance of the Indonesian Civil Servants Cooperative (KPRI) in the Pamboang sub-district of Majene Regency, West Sulawesi. The subjects of the research are KPRI Ampera and KPRI Dharma Bakti. The research variable is the cooperatives' financial performance, measured by financial ratio analysis according to the Regulation of the Minister of State for Cooperatives and SMEs of the Republic of Indonesia No 6/Per/M.KUKM/V/2006. The measurements include liquidity ratios (current ratio), solvency ratios (debt to asset ratio, debt to equity ratio), and profitability ratios (return on equity, return on asset). Data was gathered through documentation and interviews. Quantitative descriptive analysis was used to analyze the data. The research findings show that KPRI Ampera and KPRI Darma Bhakti are categorized as unhealthy cooperatives based on the regulation of the Minister of Cooperatives and SMEs of the Republic of Indonesia.Penelitian ini bertujuan untuk menganalisis kinerja keuangan Koperasi Pegawai Republik Indonesia (KPRI) di kecamatan Pamboang Kabupaten Majene Sulawesi Barat. Adapun KPRI yang menjadi subjek penelitian adalah KPRI Ampera dan KPRI Dharma Bakti. Variabel penelitian ini adalah kinerja keuangan koperasi yang diukur menggunakan analisis rasio keuangan berdasarkan Peraturan Menteri Negara Koperasi dan Usaha Kecil dan Menengah Republik Indonesia nomor 6/Per/M.KUKM/V/2006. Pengukuran meliputi Rasio Likuiditas (Current Ratio), Rasio Solvabilitas (Debt to Asset Ratio, Debt to Equity Ratio), dan Rasio Rentabilitas (Return on Equity, Return on Asset). Pengumpulan data melalui Wawancara dan dokumentasi. Data dianalisis menggunakan teknik analisis deskriptif kuantitatif. Hasil penelitian menunjukan bahwa KPRI Ampera dan KPRI Darma Bhakti tergolong Koperasi yang tidak sehat berdasarkan Permen Koperasi dan UKM RI.